9. Evaluate: x^2 – 5x 3 for x = -5

Question

Asked 4/24/2012 7:14:15 PM

Updated 6/30/2014 8:21:31 AM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by jeifunk [6/30/2014 8:21:31 AM]

s

shifa saleheen|Points 9625|

migzptz|Points 5811|

twistedechoes|Points 26|

Question

Asked 4/24/2012 7:14:15 PM

Updated 6/30/2014 8:21:31 AM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by jeifunk [6/30/2014 8:21:31 AM]

Rating

8

5(3x + 7)

=(5)(3x)+(5)(7)

15x+35

=(5)(3x)+(5)(7)

15x+35

Added 6/30/2014 8:21:30 AM

This answer has been confirmed as correct and helpful.

using PEMDAS 2 + 4 x 6^2 – 8 **Weegy:** 6 x 3 + 10 ? 2 = 18+5 = 23 (More)

Question

Updated 4/24/2012 8:12:11 AM

1 Answer/Comment

2 + 4 x 6^2 – 8

= 2 + 4 * 36 - 8

= 2 + 144 - 8

= 138

= 2 + 4 * 36 - 8

= 2 + 144 - 8

= 138

Added 4/24/2012 8:12:11 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [5/31/2014 5:14:28 PM]

5. Simplify: 5(3x + 7) **Weegy:** 9x^4. If you are satisfied with my answer, please click 'Good' on the ratings. Thank you! (More)

Question

Updated 6/5/2014 6:25:54 PM

1 Answer/Comment

5(3x + 7) = 15x + 35

Added 6/5/2014 6:25:52 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [6/6/2014 12:09:30 PM]

factor 16x^2 – 9 **Weegy:** 16x^(2)-12x-10
Factor out the GCF of 2 from each term in the polynomial.
2(8x^(2))+2(-6x)+2(-5)
Factor out the GCF of 2 from 16x^(2)-12x-10.
2(8x^(2)-6x-5)
Find the factors such that the product of the factors is the trinomial 8x^(2)-6x-5. [ This can be done by trial and error and checked using the FOIL method of simplifying polynomials.
2(2x+1)(4x-5) ] (More)

Question

Updated 6/28/2014 3:00:28 PM

1 Answer/Comment

Answer: (4x-3)(4x+3)

Added 4/24/2012 9:22:32 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [6/28/2014 3:00:28 PM]

solve for x X^2 – 12 = - 4x **Weegy:** The value of x in the given equation is x=15/16 and y=3/16 (More)

Question

Updated 8/5/2015 1:40:31 AM

1 Answer/Comment

(4÷ 2) + 8( 5-3)^2 **Weegy:** (4 ? 2) + (8 * (5 - 3) * 2) = 34 **User:** -8 – 72 ÷ 9 x 4^2 + 11 **Weegy:** -333 is the answer to -8 ? 72 ? 9 x 42 + 11 using PEMDAS (More)

Question

Updated 4/24/2012 8:17:10 AM

2 Answers/Comments

-8 – 72 ÷ 9 x 4^2 + 11

= -8 – 72 ÷ 9 x 16 + 11

= -8 - 8 x 16 + 11

= -8 - 128 + 11

= -125

= -8 – 72 ÷ 9 x 16 + 11

= -8 - 8 x 16 + 11

= -8 - 128 + 11

= -125

Added 4/24/2012 8:17:10 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [6/12/2014 12:17:21 PM]

33,380,221

questions answered

There are no comments.